Covalent functionalization and characterization of multi-walled carbon nanotubes using 5, 10, 15, 20-tetra(4-aminophenyl)porphyrinatonickel(II). Issue 11 (2nd November 2018) - Jafer, Alifia C.; Veetil, Vyshnavi T.; Prabhavathi, G.; Yamuna, R.
Abstract: 5, 10, 15, 20-tetra(4-aminophenyl)porphyrinatonickel(II) was covalently connected to multi-walled carbon nanotube (MWCNT) through an amide linkage and characterized by using many spectroscopic techniques. In FT-IR, the carbonyl peak (C = O) of MWCNT-NiTAP is shifted to higher frequency as compared to the reported MWCNT-TAP due to Ni ion substitution. Notable changes in the FT-IR and XP spectra confirms the covalent functionalization of Ni-TAP with MWCNTs. Raman spectra indicate that the ID/IG ratio is less for MWCNT-NiTAP as compared to MWCNT, MWCNT-COOH, MWCNT-ZnTAP and MWCNT-CuTAP which is due to improved electronic properties of MWCNT-NiTAP. TGA plots of MWCNT-NiTAP reveals that ∼30% weight loss in the temperature range of 150–800 °C. Considerable shift in the absorption and emission spectra of the nano hybrid clearly indicate different electronic interaction between porphyrin and MWCNT due to nickel ion substitution. PL spectra of MWCNT-NiTAP exhibited fluorescence quenching of Ni-TAP Soret band by MWCNTs. This quenching is owing to the energy or electron transfer between Ni-TAP and MWCNTs.